Photosynthetic acclimation and sensitivity to short- and long-term environmental changes in a drought-prone forest. (2nd February 2022) - Schönbeck, Leonie; Grossiord, Charlotte; Gessler, Arthur; Gisler, Jonas; Meusburger, Katrin; D'Odorico, Petra; Rigling, Andreas; Salmon, Yann; Stocker, Benjamin D; Zweifel, Roman; Schaub, Marcus
Abstract : Acclimation to irrigation increased gas exchange in Pinus sylvestris, but reduced the sensitivity to short-term changes. In addition, structural adjustments led to an attenuation of initially strong leaf-level acclimation. Abstract: Future climate will be characterized by an increase in frequency and duration of drought and warming that exacerbates atmospheric evaporative demand. How trees acclimate to long-term soil moisture changes and whether these long-term changes alter trees' sensitivity to short-term (day to months) variations of vapor pressure deficit (VPD) and soil moisture is largely unknown. Leaf gas exchange measurements were performed within a long-term (17 years) irrigation experiment in a drought-prone Scots pine-dominated forest in one of Switzerland's driest areas on trees in naturally dry (control), irrigated, and 'irrigation-stop' (after 11 years of irrigation) conditions. Seventeen years of irrigation increased photosynthesis ( A ) and stomatal conductance ( g s ) and reduced g s sensitivity to increasing VPD and soil drying. Following irrigation-stop, gas exchange decreased only after 3 years. After 5 years, maximum carboxylation ( V cmax ) and electron transport ( J max ) rates in irrigation-stop recovered to similar levels as to before the irrigation-stop. These results suggest that long-term release from soil drought reduces the sensitivity to VPD and that atmospheric constraints may play an increasingly important role in combination with soil drought. Moreover, our study indicates that structural adjustments lead to an attenuation of initially strong leaf-level acclimation to strong multiple-year drought.